The Genetic Basis of Delayed Puberty - Howard, Sasha R. (Frontiers in Endocrinology, 2019)
Delayed pubertal onset may have many etiologies, but on average two-thirds of patients presenting with late puberty have self-limited (or constitutional) delayed puberty. Self-limited delayed puberty often has a strong familial basis. Segregation analyses from previous studies show complex models of inheritance including autosomal dominant, autosomal recessive, bilineal and X-linked, although sporadic cases are also observed. The majority of pedigrees with familial delayed puberty display an autosomal dominant pattern of inheritance (with or without complete penetrance). Despite this, the neuroendocrine pathophysiology and its genetic regulation remain unclear in the majority of patients with self-limited delayed puberty. Only rarely have mutations in genes known to cause aberrations of the hypothalamic-pituitary-gonadal axis been identified in cases of delayed puberty, and the majority of these are in relatives of patients with congenital hypogonadotropic hypogonadism (CHH), for example in the FGFR1 and GNRHR genes. Using next generation sequencing methods, a deleterious mutation in the CHH gene HS6ST1 was found as the likely causal factor for self-limited delayed puberty in one extended pedigree. A comparative study of the frequency of mutations in GnRH deficiency genes between probands with CHH and those with self-limited delayed puberty found a significantly higher proportion of mutations with a greater degree of oligogenicity in the CHH group. Mutations in the gene IGSF10 have been implicated in the pathogenesis of familial late puberty in a large Finnish cohort. IGSF10 disruption represents a fetal origin of delayed puberty, with dysregulation of GnRH neuronal migration during embryonic development presenting for the first time in adolescence as late puberty. Rare heterozygous variants in FTO have been identified in pedigrees with self-limited delayed puberty associated with extreme low BMI and maturational delay in growth in early childhood. Recent exciting evidence highlights the importance of epigenetic up-regulation of GnRH transcription by a network of miRNAs and transcription factors, including EAP1, during puberty. Whilst a fascinating heterogeneity of genetic defects have been shown to result in delayed and disordered puberty, and many are yet to be discovered, genetic testing may represent a future diagnostic tool for the differentiation of the conditions that lead to delayed puberty.